BIFURCATION TO CHAOS IN THE СOMPLEX GINZBURG–LANDAU EQUATION WITH LARGE THIRD-ORDER DISPERSION - I. I. Ovsyannikov; D. V. Turaev; S. V. Zelik (Моделирование и анализ информационных систем)
We give an analytic proof of the existence of Shilnikov chaos in complex Ginzburg– Landau equation subject to a large third-order dispersion perturbation.